Perkembangan Kognitif Anak dalam Menghafal al-Qur’an Prespektif Jean Piaget: Pendidikan, Perkembangan kognitif, Prespektif JeanPiaget - jay, Wasiatul; Ningrum, Jaya; Muhid, Abdul (Mu'allim, 2024)
This journal discusses the cognitive processes of Quran memorizers, focusing on the development of problem-solving skills and the transition from simple to complex thinking to achieve adult-level maturity in thinking. Through a literature review method, this research analyzes data from various related journals to understand the cognitive processes of Quran memorizers. The results indicate that problem-solving abilities at this stage align with individual cognitive development. Additionally, specific strategies can be employed to reinforce learned information. Psychological implications, character education, and Quran memorization learning in early childhood are also highlighted in this journal. Thus, understanding the cognitive processes of Quran memorizers enriches not only intellectual intelligence but also strengthens emotional and spiritual intelligence. This research provides an important theoretical foundation for understanding and enhancing the Quran memorization process.